Mitochondrial DNA diversity in wild gaur (Bos gaurus gaurus): evidence from extant and historical samples. Issue 2 (2nd April 2020) - Atkulwar, Ashwin; Farah, Sameera; Gadhikar, Yashashree; Baig, Mumtaz
Abstract: Bos gaurus gaurus commonly called as gaur is a wild bovid species inhabiting South and Southeast Asia and attained vulnerable status in India. In this study, we typed 62 extant free-ranging wild gaur individuals for mitochondrial partial displacement loop (D-loop) and cytochrome b gene (Cyt b ) from the Melghat Tiger Reserve (MTR). Two historical DNA samples originating from museums and two Tectona grandis bark fibers samples browsed by wild gaur were also used as a source of environmental DNA. Both D-loop and Cyt b loci show the occurrence of a single haplotype in the contemporary wild gaur population. While D-loop fragment sequencing of two historical museum samples reveals two unique haplotypes, virtually absent in the present wild gaur population of MTR. Amplifications of the similar haplotypes in gaur DNA samples obtained through chewed T. grandis bark fibers have proved the efficacy of eDNA. Bayesian Skyline Plot (BSP) analysis using extant and historical D-loop sequences illustrate population decline starting from upper Mesolithic. Also, the BSP graph indicates accelerated effective population size decline ( Ne ), a time period coinciding with the different phases of the ∼5000 years old Indus civilization. The plot shows an overall declining trend in the wild gaur population, a probable outcome of ever-shrinking habitat in the central Indian landscape caused by prehistoric, medieval and colonial hunting practices.